Forced migration, gender, social capital and coping strategies in Western Tanzania - Wambugu, Lydia Wakarindi (My University, 2008)
Abstract would not load on DSpace.
Keywords: Forced Migration/Displacement; Refugee Women; Coping Strategies; Social Capital; Human Rights; Tanzania; Burundi; Rwanda; Democratic Republic of the Congo (DRC); Qualitative Research Methods